Analisis Panjang Badan Lahir dan Berat Badan Lahir terhadap Wasting pada Baduta di Kota Surabaya - Alifa Hawa Nur Rohmah; Siti Rahayu Nadhiroh (Media Gizi Kesmas, 2024)
Background: Wasting remains a significant public health problem in Surabaya. Wasting may hinder optimal performance during a child's golden years, the first 1,000 days of life, which has a significant impact on the quality of Indonesia's future human resources. Child conditions such as low birth weight and short birth length may increase the risk of wasting. Objectives: To analyze the relationship between birth length and birth weight and the incidence of wasting in children under two years in Surabaya city. Methods: Cross-sectional study design using secondary data. The total sample included 160 children selected by consecutive sampling from the working areas of Putat Jaya, Semimi, Tanah Kalikeding and Bangkingan Surabaya Health Center.Data were analyzed using Pearson correlation test. Results: The proportion of wasting was 13.8%. The study findings revealed a relationship between birth weight and the occurrence of wasting in Surabaya city (p = 0.030 The study did not identify any relationship between birth length and the occurrence of wasting (p = 0.675). Conclusions: Evidence from the study supports a relation between birth weight and wasting in children under two years in Surabaya City. However, birth length is not associated with the occurrence of wasting.